Visual communication-based social campaign design for waste sorting awareness - Nur Aswad, Iqbal; Sahabudin, Arfah; Wahyuni Zainuddin, Sri (Universitas Ahmad Dahlan, 2025)
This study analyzes the effectiveness of a visual communication-based social campaign in improving public knowledge, attitudes, and behavior regarding waste sorting at Baqbatoa Beach and Rumede Village tourist attractions in Polewali Mandar Regency. A mixed-method approach was employed, combining quantitative and qualitative techniques through pre- and post-campaign questionnaires, field observations, and social media data analysis. The findings reveal that while visitors already possessed good initial knowledge, the campaign enhanced their technical understanding. In terms of attitudes, scores increased at Baqbatoa Beach (from 4.26 to 4.43), while Rumede Village maintained a consistently high level (4.76). The most significant change occurred in behavioral aspects, with scores at Baqbatoa Beach rising from 1.56 to 4.17 and at Rumede Village from 1.84 to 4.62, confirming the campaign's tangible impact on waste-sorting practices. Dissemination through Instagram (@polman_update) also showed strong audience engagement, generating 115 likes, 6 saves, 6 shares, and 123 total interactions. Qualitative findings indicate that the campaign design was perceived as attractive, clear, easy to understand, and motivational. Overall, the study confirms that visual communication-based campaigns effectively strengthen environmental literacy and promote sustainable waste management practices. This research contributes to the field of communication and environmental studies by demonstrating how visual communication strategies can be effectively applied to foster behavioral change in waste management at tourist destinations. The findings provide practical insights for policymakers, tourism managers, and environmental organizations in designing impactful campaigns that support sustainable tourism.